Labour shortages and wage growth - Erik Frohm (European Central Bank (ECB), 2021)
Tight labour markets are usually accompanied by mounting wage pressures. Yet, in the past decade, wage growth has remained subdued despite the appearance of widespread labour shortages. This paper re-examines labour market conditions since 2007 through the lens of a novel indicator, relative labour shortages (RLS), based on data from a large representative business survey in Sweden. Four main results emerge from the analysis: (1), the time-series average of RLS suggested much weaker labour market conditions during the 2013−2019 recovery from the Great Recession and during the Covid-19 pandemic in 2020 than qualitative surveys or the vacancy-unemployment ratio. (2), the reason is that RLS contains a time-varying intensive margin of labour shortages not recorded in most surveys, which has been trending downwards since the Great Recession. (3), fixed-effects regressions with several aggregate-, sector, region and establishment-level controls confirm that RLS is strongly and positively correlated with annual wage growth at the establishmentlevel. (4), sector-level wage Phillips curves show that the subdued level of RLS can help explain the sluggish wage growth in Sweden since the Great Recession.
Keywords: C80; E31; E60; J23; J31; 330; Wage inflation; labour markets; survey data